PARADIGMA KOMUNIKATIF DALAM MENINGKATKAN KETERAMPILAN BERBICARA (MAHARAH AL-KALAM) BAHASA ARAB - Ahmad Sururi; Hamzah Fathurrohman Arroja; Acep Hermawan; Eva Latifah Fauzia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study discusses the communicative paradigm in Arabic language learning as an approach that emphasizes the use of language for real communicative purposes. The main focus is speaking skills or maharah al-kalam, namely the ability to convey ideas orally with precision, fluency, and contextual appropriateness. The communicative paradigm is considered relevant because it encourages learners to actively use Arabic through dialogue, question and answer, simulation, and meaningful interaction activities. This study uses a library research approach by examining the basic concepts of maharah al-kalam and the application of the communicative approach in Arabic language learning. The results show that the communicative paradigm can improve students' courage, fluency, active vocabulary, and speech accuracy in speaking Arabic.